Evaluation De La Performance Des Pratiques De Gestion De La Fertilite Des Sols Dans Le Bassin De La Riviere Okpara Au Benin - M.A. Akpo; A. Saidou; I. Balogoun; I. Yabi; L.B. Bio Bigou (European Scientific Journal, ESJ, 2016)
A good management of agricultural land based on scientific knowledge and farmer indigenuous knowledge is necessary to ensure sustainable agricultural production. Our research aims to evaluate the performance of farmers' strategies and improved soil fertility management practices in improving level of crop yields in the basin of the Okpara River in Benin. Surveys using semi-structured questionnaire were conducted from October 11 to November 30, 2015 on a sample of 1048 farmers belonging to socio-cultural groups Tchabè, Mahi, Ditamari, Lokpa, Bariba and Fulani. Informations collected concerned farmers' soil fertility management practices and soil fertility improvement strategies introduced by the extension services. Crop rotation, long term natural fallow, fallow with perennial crops especially cashew trees, cassava "fallow" and cereal and leguminuous intercropping (respectively 91.11; 41.66; 48.53; 54.61 and 86.25% of respondents) are endogenous soil fertility management practices. However, mineral and organic fertilizers (respectively 25.45 and 20.38% of respondents) are improved soil fertility management practices introduced. Generally 42% of respondent mentioned that indigenuous soil fertility management practices could improve only by 25% crop (especially maize) yield level against 98.5% of respondents who mentioned that improved soil fertility management practices could improve by 50% of the crop yield level. Considering the efficiency of these soil fertility management practices our study suggests some issues to be taken into account for better land management in the study area.